Pesquería y crecimiento de la piangua (Arcoida: Arcidae) Anadara tuberculosa en la Bahía de Málaga del Pacífico colombiano, 2005-2007 The fisheries and growth of Ark Clams (Arcoida: Arcidae) Anadara tuberculosa in Málaga Bay, Colombian Pacific, 2005-2007 - Carlos Lucero; Jaime Cantera; Raúl Neira (Revista de Biología Tropical, 2012)
The fisheries and growth of Ark Clams (Arcoida: Arcidae) Anadara tuberculosa in Málaga Bay, Colombian Pacific, 2005-2007. A. tuberculosa, is the most important bivalve species under exploitation in Colombia. Here, this species is found from Cabo Corrientes (Chocó) to the Ecuador border, in muddy substrates of mangrove forests. In order to determine the growth and the state of fisheries of A. tuberculosa, between December 2005 and April 2007, both, biological (in situ) and commercial studies were performed at Bahia Malaga (Colombian Pacific). The growth was estimated using the general equation of von Bertalanffy, with prior application of the methods of Bhattacharya and Powell-Wetherall. Mortality and exploitation rate were determined using the inverse model of von Bertalanffy. For the biological samplings, a total of 446 individuals of A. tuberculosa (0.64±0.13 individuals/m²) and 53 individuals (0.05±0.049 individuals/m²) of Anadara similis were collected. 79% of the catch was below 51mm. In the commercial samplings, 836 individuals of A. tuberculosa (size range: 31.1-92.2mm) were measured, but no A. similis samples were available for this. Recruitment of A. tuberculosa was higher during March, May, July and November. According to the data, A. tuberculosa might be reproducing during December, February, April and August. The data gathered with the biological samples were more reliable on explaining the growth of A. tuberculosa (K=0.332per year, L∞=88.256mm, t0=0.0556years) than the one taken from market samples (K =0.256per year, L∞=89.77mm, t0=0733years). The high exploitation rate (77%), the low density and the high mortality suggest that A. tuberculosa is in overexploitation state in Bahia Malaga and management strategies are urgently required